Clinical Patterns and risk factors for rhegmatogenous retinal detachment at a tertiary eye care centre of northern India - Takkar, Brijesh; Azad, Shorya; Bhatia, Indrish; Azad, Rajvardhan (Nepalese Journal of Ophthalmology, 2017)
Purpose: To identify patterns and risk factors for rhegmatogenous retinal detachment (RD) in northern India. Methods: This was a retrospective study conducted at a tertiary care centre in northern India. 378 consecutive records of patient, operated between January 2011 to June 2012 were included for analysis. Clinical history, signs and risk factors of RD were evaluated. Comparison was done with available literature from other developing nations. Results: Mean age of the patients was 40.12 + 20.43 years (Range 12-85 years); 81% were male and half of the patients presented after 1 month of visual symptoms. Retinal breaks were discovered commonly in the temporal region, while no break was found in10% of the patients. PVR more than grade C was seen in a third of the patients. Prior surgery for cataract was found to be the most common identifiable risk factor for RD (40%). Bilateral RD was seen in 13% of the patients. Conclusion: Pseudophakia is the commonest risk factor for RD. If no retinal break is discovered pre operatively, the surgeon should seek a retinal break temporally during surgery. Bilateral RD is a serious concern for rural northern India, probably linked to delayed presentation.